A self-consistent model for thermodynamics of multicomponent solid solutions. (October 2016) - Svoboda, J.; Fischer, F.D.
Abstract: The self-consistent concept recently published in this journal (108, 27–30, 2015) is extended from a binary to a multicomponent system. This is possible by exploiting the trapping concept as basis for including the interaction of atoms in terms of pairs (e.g. A–A, B–B, C–C…) and couples (e.g. A–B, B–C, …) in a multicomponent system with A as solvent and B, C, … as dilute solutes. The model results in a formulation of Gibbs-energy, which can be minimized. Examples show that the couple and pair formation may influence the equilibrium Gibbs energy markedly. Graphical abstract: